Manajemen Mutu SMK Ma’arif NU 1 Bener Purworejo dalam Meningkatkan Mutu Pendidikan dan Kepercayaan Masyarakat - eliyanto .; Agus Muzamil (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This research is based on the importance of school quality management. In relation with that in mind, this study aims to determine SMK Quality Management Maarif NU 1 Bener Purworejo in Improving the Quality of Education and Trust Society. This research is a qualitative research. Data collection using interviews, observation, and documentation, and the validity of the data using triangulation, and data analysis techniques including data collection, reduction data, data presentation, and drawing conclusions. This research resulted in four conclusions: (1) Planning for SMK Maarif NU 1 Bener Purworejo in improving education quality and public trust, namely: First, setting quality standards, which refers to the 8 National Education Standards. Second, quality mapping, which based on the results of the School Self-Evaluation and SNP (National Education Standards). Third, preparation of a quality compliance plan. (2) Implementation of Maarif NU 1 Bener Vocational School Purworejo in improving the quality of education and public trust is carried out through fulfillment of Content Standards, Process Standards, Graduate Competency Standards, Standards Educators and Education Personnel, Facilities and Infrastructure Standards, Management Standards, Educational Assessment Standards, Financing Standards. Next, all the components schools also have a high commitment to the implementation of quality fulfillment. (3) Evaluation of SMK Maarif NU 1 Bener Purworejo in improving the quality of education and Community trust is carried out through the School Self-Evaluation. At this stage, school develop evaluation instruments and then form an evaluation implementation team. (4) Follow up Continue SMK Maarif NU 1 Bener Purworejo in improving the quality of education and public trust is carried out as a continuous cycle, namely through: Corrective Action, this corrective action is taken if the results do not achieve what was expected has been targeted; and Standardization Action, this corrective action is carried out if the results reached the target that had been set.